Orality as a Ground for Dialogue and Positive Encounter: A Case Study of the Orang Rimba in Jambi, Indonesia - Khairullah Zikri (International Journal of Sociology of Religion, 2024)
This article discusses the role of oral tradition in the Orang Rimba community who inhabit the Makekal Ilir forest area, in Jambi Province. The author reads the orality in the frame of the relationship between the Orang Rimba and the residents of Tanah Garo Village. The latter are considered to have a brotherhood or kinship relationship with the former. The fundamental question is whether orality is the key word in building a positive encounter and dialogue on meaningful relations between the Orang Rimba and the residents of Tanah Garo, or on the contrary becomes a vehicle for exploitation? The author asserts that positive potential is possible if orality, which is the common thread of the relationship between the two communities, is properly disseminated to the descendants of the two communities. Without good transmission, the negative potential and exploitation will be more prominent.